2011
DOI: 10.1186/1745-6215-12-146
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of wet-cupping therapy for persistent non-specific low back pain: a randomised, waiting-list controlled, open-label, parallel-group pilot trial

Abstract: BackgroundPersistent non-specific low back pain (PNSLBP) is one of the most frequently experienced types of back pain around the world. Wet-cupping is a common intervention for various pain conditions, especially in Korea. In this context, we conducted a pilot study to determine the effectiveness and safety of wet-cupping treatment for PNSLBP.MethodsWe recruited 32 participants (21 in the wet-cupping group and 11 in the waiting-list group) who had been having PNSLBP for at least 3 months. The participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
1
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 32 publications
1
75
1
7
Order By: Relevance
“…We allowed freedom for the selection of points and stimulation methods (wet or dry cupping) to reflect the real-world clinical situation. As it is a very difficult to separate individual factors affecting the specific effects of cupping, most clinical research does not adopt strict standardized treatment guidelines for the cupping procedure, including the size of cups, applied areas, volume of drained air, and retention time of cups 15,30,31,37) . To resolve this problem, two kinds of efforts should be made in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We allowed freedom for the selection of points and stimulation methods (wet or dry cupping) to reflect the real-world clinical situation. As it is a very difficult to separate individual factors affecting the specific effects of cupping, most clinical research does not adopt strict standardized treatment guidelines for the cupping procedure, including the size of cups, applied areas, volume of drained air, and retention time of cups 15,30,31,37) . To resolve this problem, two kinds of efforts should be made in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Dry cupping without puncture of the skin was applied mainly, but wet cupping was also applied for up to 2 points in the case of lesions with blood-stasis symptoms, severe tenderness and prominent warmness. According to the predefined clean technique procedure 15) , cupping cups were attached after 3 to 5 cycles of pumping for negative pressure by cupping pump and retained for 5 to 10 minutes according to the patient's general condition and symptom severity. For wet cupping, the skin was punctured 6 times to a 2-mm depth around the cupping sites with 26-gauge disposable lancets (Tianjin Haing Lim Sou Won Medical Instrument Co., China).…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…After binding to opioid receptors in the limbic system, the middle brain, and spinal cord, opioids reduce pain by preventing a variety of pain-producing neurotransmitters, so that reduced pain scale. Kim et al (2011) reported that the mu opioid receptors and delta opioid receptors bind strongly to the endorphins that come from POMC [9]. Endorphins and encephalin have an important role in endogenous pain reduction [10].…”
Section: Resultsmentioning
confidence: 99%
“…ADL and Sports/Recreation: Hijama Bi'l Shart might improve ADL and Sports/Recreation function through reduction of inflammation in tissues & cells 60,61 and boost the immune system by increasing the number of macrophages 45,47 .…”
Section: Stiffnessmentioning
confidence: 99%